Findings from an online behavioural weight management programme provided with or without a fortified diet beverage. Issue 2 (28th January 2014) - Haddock, C. Keith; Poston, Walker S. C.; LaGrotte, Caitlin; Klotz, Alicia A.; Oliver, Tracy L.; Vander Veur, Stephanie S.; Foster, Gary D.; Jebb, Susan A.; Moore, Carmel; Roberts, Susan A.; Reeves, Rebecca S.; Bolton, Mary Pat; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> The present multi-centre randomised weight-loss trial evaluated the efficacy of a low-intensity 12-week online behavioural modification programme, with or without a fortified diet beverage using a 2 × 2 factorial design. A total of 572 participants were randomised to: (1) an online basic lifestyle information (OBLI) intervention, consisting of one online informational class about tips for weight management; (2) an online behavioural weight management (OBWM) intervention, entailing 12 weekly online classes focused on weight-loss behaviour modification; (3) an OBLI intervention plus a fortified diet cola beverage (BEV) containing green tea extract (total catechin 167 mg), soluble fibre dextrin (10 g) and caffeine (100 mg) (OBLI+BEV); (4) OBWM+BEV. Assessments included height, weight, dual-energy X-ray absorptiometry-derived body composition, and waist circumference (WC). Attrition was 15·7 %. Intention-to-treat (ITT) models demonstrated a main effect for type of Internet programme, with those assigned to the OBWM condition losing significantly more weight (F= 7·174; P= 0·008) and fat mass (F= 4·491; P= 0·035) than those assigned to the OBLI condition. However, there was no significant main effect for the OBWM condition on body fat percentage (F= 2·906; P= 0·089) or WC (F= 3·351; P= 0·068), and no significant main effect for beverage use or significant interactions between factors in ITT models. A 12-week, low-intensity behaviourally based online programme produced a greater weight loss than a basic information website. The addition of a fortified diet beverage had no additional impact.